SAT0111 THE RELATIONSHIP BETWEEN THE ADMINISTRATION OF IL-6 INHIBITORS AND INSULIN RESISTANCE IN PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS. (13th June 2020) - Jitaru, A.; Pomirleanu, C.; Leon-Constantin, M. M.; Mitu, F.; Ancuta, C.
Abstract : Background: Rheumatoid arthritis (RA) is associated with an increased cardiovascular (CV) risk, due not only to the traditional risk factors (hypertension, insulin resistance/diabetes, obesity, smoking), but to the inflammatory status as well. The blockade of interleukin-6 (IL-6) can regulate the glucose metabolism, reducing the glucose level and insulin resistance (IR). This beneficial effect is seen more in patients with normal values of body mass index (BMI), compared to the obese population. Objectives: Given the mentioned existing data, we aim to demonstrate the positive effect of IL-6 inhibitors in active RA patients with normal or increased BMI. Methods: We recruited 56 consecutive patients with definite and active RA, non-responders/partial responders to conventional synthetic Drug Modifying Anti-Rheumatic Drugs (csDMARDs)/biological therapy. For a period of 52 weeks, patients received subcutaneous Tocilizumab (TCZ) in a dose of 162mg once a week, according to European League Anti Rheumatism (EULAR) recommendation and National Protocol. We assessed demographics, RA-related parameters (clinical, inflammatory and immune) and metabolic markers, as well as the peripheral response to insulin, quantified by Homeostasis Model Assessment for insulin resistance (HOMA-IR) and the Quantitative Insulin Sensitivity Check Index (QUICKI). We did not include in the study the patients known with diabetes mellitus (DM) and those undergoing glucocorticoids. Results: After 52 weeks of treatment, most of the patients showed a statistically significant reduction of HOMA-IR (3.61 ± 1.21 at the onset vs. 2.45 ± 1.46 at the end of the study, p<0.001), while QUICKI registered a slight increase (0.32 ± 0.01 at the onset vs. 0.33 ± 0.01 at the end of the study, p<0.001). Also, the decrease in insulin and glucose levels were more obvious in patients with normal BMI, strictly related to disease activity. Conclusion: Long-term administration of TCZ in active RA is associated with a significant reduction of disease activity and IR, especially in normal weight patients. This confirms that obesity, as a CV risk factor, represents one of the main causes of IR. References: [1]Castañeda S, Remuzgo-Martínez S, López-Mejías R et al. Rapid beneficial effect of the IL-6 receptor blockade on insulin resistance and insulin sensitivity in non-diabetic patients with rheumatoid arthritis. Clin Exp Rheumatol . 2019; 37(3):465-473. [2]Lehrskov LL, Christensen RH. The role of interleukin-6 in glucose homeostasis and lipid metabolism. Semin Immunopathol . 2019; 41(4):491-499. [3]Ursini F, Russo E, Ruscitti P, Giacomelli R, De Sarro G. The effect of non-TNF-targeted biologics and small molecules on insulin resistance in inflammatory arthritis. Autoimmun Rev . 2018 Apr;17(4):399-404. Disclosure of Interests: Alexandra Jitaru: None declared, Cristina Pomirleanu: None declared, Maria-Magdalena Leon-Constantin: None declared, Florin Mitu: None declared, CODRINA ANCUTA Consultant of: AbbVie, Pfizer, Roche, Novartis, UCB, Ewopharma, Merck Sharpe and Dohme, and Eli Lilly, Speakers bureau: AbbVie, Pfizer, Roche, Novartis, UCB, Ewopharma, Merck Sharpe and Dohme, and Eli Lilly